Using systematic conservation planning to minimize REDD+ conflict with agriculture and logging in the tropics. Issue 2 (13th September 2012) - Venter, Oscar; Possingham, Hugh P.; Hovani, Lex; Dewi, Sonya; Griscom, Bronson; Paoli, Gary; Wells, Phillip; Wilson, Kerrie A.
Abstract This article describes the first application of systematic conservation planning for prioritizing REDD+ (reducing emissions from deforestation and forest degradation) strategies and agricultural expansion. For a REDD+ program in Indonesian Borneo, we find that the most cost‐effective way to reduce forest‐based emissions by 25% is to better manage protected areas and logging concessions. A more ambitious emissions reduction target would require constraining agricultural expansion and logging, which incurs opportunity costs. We discover, however, that these impacts can be mitigated by relocating oil palm (Elaeis guineensis) agricultural leases to areas that store, on average, 130 tons less carbon per hectare and are 8% more productive for oil palm. This reduces the costs of meeting REDD+ targets, avoids conflict with agriculture, and has the unanticipated effect of minimizing impacts on logging. Our approach presents a transparent and defensible method for prioritizing REDD+ locations and strategies in a way that minimizes development trade‐offs and promotes implementation success.